EFEKTIFITAS JANTUNG PISANG DAN DAUN KATUK TERHADAP PRODUKSI ASI PADA IBU MENYUSUI DI DESA TELUK KIAMBANG WILAYAH KERJA PUSKESMAS TEMPULING KECAMATAN TEMPULING KABUPATEN INDRAGIRI HILIR - Haryati Astuti (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2020)
The breastfeeding mothers can be interpreted as the process of giving breast milk (ASI) to infants, where the baby has a sucking reflex to get and swallow the milk. The breastfeeding is a natural process of breast milk that is the best food for babies who are able to meet the nutrients needed by the baby's body during the first 6 months. Breastfeeding babies in Indonesia has become a culture but the practice of breastfeeding is still far from expected. According to WHO and UNICEF (2012), there were 136.7 million babies born worldwide in 2011 and only 32.6% of babies were exclusively breastfed during the first 6 months. The method used in this study is Quasy Experiment, with the type of design Nonprobability Sampling and consecutive sampling technique posttest with control design obtained the results of respondent breast milk production before given the consumption of banana heart vegetables, the majority of the majority is (71.4%) and after the majority is (64.3%). Breast milk production of respondents before given the majority consumption of katuk leaves clear vegetables as much as (64.3%) and after as much as (92.9%) with a parametric statistical test that is paired t-test p value 0.040. the most effective was katuk leaf vegetable (92.9%). It is hoped that the results of this study can be used as an evaluation material with future activities.